Enhanced photocatalytic performance of molecularly imprinted hydroxyapatite thin film for bilirubin degradation. Issue 1 (15th February 2012) - Yang, Zhengpeng; Zhang, Chunjing
ABSTRACT A molecularly imprinted hydroxyapatite (HAP) thin film was constructed onto the surface of quartz crystal using molecular imprinting and surface sol–gel process. Quartz crystal microbalance technique was employed to in situ investigate the interaction between bilirubin (BR) and HAP film. Compared with non‐imprinted HAP film, the molecularly imprinted HAP film not only exhibits a much higher adsorption capacity for BR molecule, but shows an enhanced photocatalytic activity in degrading BR. According to the in situ frequency measurement, the degradation‐rate constants (K) of BR on imprinted HAP film is about 8.05 × 10−4 s−1, which is two times higher than that obtained on non‐imprinted HAP film. © 2012 Curtin University of Technology and John Wiley & Sons, Ltd.